Symbolism of Identity and Death in the Short Story Kayu Nisan Terakhir: A Structural and Interpretative Study - Sofyaningrun, Rosita; Mustofa, Akhmad Sulton Ali (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the reflection of identity and death through symbolism in the short story Kayu Nisan Terakhir. The research employs a qualitative approach using a descriptive-analytical method, through structural and semiotic readings of narrative elements and the network of symbols within the text. The findings reveal that the themes of identity and death form the central framework of meaning, which is integratively expressed through symbols such as the gravestone, burial space, and silence. These symbols do not stand independently but are interconnected in constructing an existential reflection on human mortality and the limitations of social identity. Death is represented as a universal inevitability that dissolves the boundaries of worldly identity while simultaneously evoking both tranquility and emptiness. The structural relationship between theme and symbolism produces a unified, profound, and reflective meaning. Thus, the short story demonstrates how symbolism functions as both an aesthetic and philosophical device in constructing meanings about life and death.